2017
DOI: 10.3136/fstr.23.517
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Phosphatidic Acid in Japanese Mustard Spinach (Komatsuna) during the Milling Process

Abstract: Lysophosphatidic acid has a role in protecting the gastrointestinal tract, and is formed from the digestion of exogenous foodstuff-derived phosphatidic acid (PA) in the human digestive tract. Japanese mustard spinach (Komatsuna) is an important source of foodstuff-derived PA. PA does not accumulate at high levels in Komatsuna, but is abundantly released upon grinding of Komatsuna. To manufacture PA-rich food using Komatsuna, the characteristics of micro wet milling (MWM) and PA production of Komatsuna were inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 26 publications
3
5
0
Order By: Relevance
“…The suitable combination of variables for high PA content is X1-1X2-1X3-1 or X1-2X2-1X3-2, which has good agreement with the analyzed results for particle size. These results verified the outcomes from a previous study reported by Li et al (2017), which showed the increase of PA content depended on the reduction in particle size due to the high proportion of native Komatsuna PA released from the biomembrane through particle splitting as well as the release of endogenous PC during grinding that is converted to more PA by PLD. Moreover, the PA contents from the optimum conditions were verified to be 69.878 ± 2.6 µg/mL and 70.089 ± 3.4 µg/mL.…”
Section: The Optimization Of Mwm Milling Parameters For Komatsuna Juisupporting
confidence: 91%
See 3 more Smart Citations
“…The suitable combination of variables for high PA content is X1-1X2-1X3-1 or X1-2X2-1X3-2, which has good agreement with the analyzed results for particle size. These results verified the outcomes from a previous study reported by Li et al (2017), which showed the increase of PA content depended on the reduction in particle size due to the high proportion of native Komatsuna PA released from the biomembrane through particle splitting as well as the release of endogenous PC during grinding that is converted to more PA by PLD. Moreover, the PA contents from the optimum conditions were verified to be 69.878 ± 2.6 µg/mL and 70.089 ± 3.4 µg/mL.…”
Section: The Optimization Of Mwm Milling Parameters For Komatsuna Juisupporting
confidence: 91%
“…The particle size reduction also depends on the properties of the materials, and some excipients and stabilizers could improve the reduction of particle size by stabilizing the physical properties of the milling particles (Cerdeira et al, 2011). In addition, the results for PA content agreed with the phenomenon reported previously by Li et al (2017) in which the particle size was smaller, and the PA content was higher. In this study, with the different milling rotational speeds, the PA contents changed within a limited range.…”
Section: Effects Of Milling Rotation On the Particle Size And Pa Contsupporting
confidence: 86%
See 2 more Smart Citations
“…Such a process can be seen in the processing of Komatsuna (Brassica rapa var. perviridis) (Li et al, 2017), which is abundant in phosphatidic acid. The one standard has also been employed to efficiently reduce the particle size as in the production of fine rice slurry (Koyama & Kitamura, 2014), the processing of rice milk by MWM to develop a cheese-like product (Nakamura et al, 2016), and the processing of orange juice with pulp (Islam et al, 2017).…”
mentioning
confidence: 99%